2021
DOI: 10.1177/08850666211024176
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of the Inferior Vena Cava for Fluid Responsiveness: Making the Case for Skepticism

Abstract: Determining whether a patient in shock is in a state of fluid responsiveness (FR) has long been the Holy Grail for clinicians who care for acutely ill patients. While various tools have been put forth as solutions to this important problem, ultrasound assessment of the inferior vena cava has received particular attention of late. Dozens of studies have examined its ability to determine whether a patient should receive volume expansion, and general enthusiasm has been strengthened by the fact that it is easy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Considering the aforementioned, while it is tempting to infer that inspiratory IVC collapse and/or a normal ejection fraction necessarily indicate IV fluids in circulatory failure, these assumptions can be wrong. Inspiratory IVC collapse has multiple co-varying determinants, including changing pleural, abdominal and central venous pressures [ 29 , 30 , 31 , 32 ]. Assuming that the pleural and abdominal pressures change consistently (within a patient and between patients) then the primary hemodynamic determinant of IVC collapse is the right atrial pressure or CVP [ 33 ].…”
Section: Basic Critical Care Echocardiography and Its Caveatsmentioning
confidence: 99%
“…Considering the aforementioned, while it is tempting to infer that inspiratory IVC collapse and/or a normal ejection fraction necessarily indicate IV fluids in circulatory failure, these assumptions can be wrong. Inspiratory IVC collapse has multiple co-varying determinants, including changing pleural, abdominal and central venous pressures [ 29 , 30 , 31 , 32 ]. Assuming that the pleural and abdominal pressures change consistently (within a patient and between patients) then the primary hemodynamic determinant of IVC collapse is the right atrial pressure or CVP [ 33 ].…”
Section: Basic Critical Care Echocardiography and Its Caveatsmentioning
confidence: 99%
“…This small, pilot study cannot explain the underlying mechanism of this observation, though the inspiratory collapse of the IVC is driven by multiple determinants, only one of which is the pressure within the vein. Subtle differences in blood volume, inspiratory pattern, abdominal compliance and the distribution between portal and non-portal venous return may mediate the size and collapse of the IVC [18,[43][44][45][46][47][48][49][50][51][52]. The dissociation between the IVC collapse and ccFT ∆ is clinically relevant, as measuring ccFT ∆ ostensibly improves the sensitivity of IVC collapse for predicting fluid responders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cardiac factors, most importantly right ventricular dysfunction, can also confound the results; such patients typically have a chronically dilated IVC which renders interpretation difficult [23]. Moreover, USs do not allow real-time continuous monitoring [23], and the collapsibility and diameter thresholds have not been validated in critically ill patients [24]. [25] reported that baseline SV and CO were better at predicting the response to fluid resuscitation than traditional markers.…”
Section: Ultrasoundsmentioning
confidence: 99%